Does the Sustainability Report Influence Financial Performance in Indonesian Energy Companies? - Sapto Haji (The Graduate School of Sahid University, 2023)
This study empirically analyzes the influence of Sustainability Reporting on the financial performance of energy sector companies listed on the Indonesia Stock Exchange using a panel data regression. This study uses secondary data from Sustainability Reporting and financial reports of energy sector companies listed on the Indonesia Stock Exchange. Research findings on the Random Effect Model show that environmental, social, and governance performance scores do not have a significant effect on a company's financial performance. This is possible due to limited transparency regarding Sustainability Report performance scores. Leverage and company size contribute significantly to the company's financial performance. The publication of easily accessible financial reports makes investors take these two things into account as determinants of a company's financial performance. These research findings provide input for the Financial Services Authority to further encourage the publication of Sustainability Reports and publish company rankings based on their Sustainability Report performance. Future research may observe certain sectors with specific characteristics, and add intervening or moderating variables according to previous research findings.